Viability of Sucupira-Branca (Pterodon emarginatus VOGEL.) seeds collected directly from the mother tree and on the soil - Valentim , Sebastião Marcos Silva; Luz , Petterson Baptista da; Cardoso, Elaidy Laura Oliveira; Moretto, Gabriel; Moreira, Antônio Carlos Silva; Amaral, Anna Júlia Cardoso; Miranda, Bruna Samy de Oliveira; Freire, Loryane Ribeiro; Oliveira, Karina Leite de (Seven Editora, 2023)
The species Pterodon emarginatus Vogel., popularly known as Sucupira-Branca, is a tree belonging to the Fabaceae family and is widely distributed in the Cerrado Biome. Its fruits are widely used in the fight against rheumatism, and diabetes and are mainly used in the treatment of inflammations, its wood is resistant and can be used in constructions, in addition, the species has the potential for reforestation actions. The objective of this work was to evaluate the viability of Sucupira-Branca seeds collected directly from the mother tree and on the ground, in a transition region between the Cerrado Biome and the Amazon Forest in Cáceres-MT. To carry out the study, 1,200 Sucupira-Branca fruits were collected, of which 600 were collected directly from the mother tree and the other 600 were collected on the soil located below it. The fruits were opened and the viability of their seeds was evaluated qualitatively and visually, analyzing whether they were whole, without imperfections, and with normal color (light brown), where the number of viable and non-viable seeds of the fruits was counted. fruits collected both directly from the parent tree and those that were on the ground so that it could analyze whether there is a difference in the viability of the seeds collected in both places. In total, 1,200 seeds were evaluated, of which, of the 600 seeds collected on the ground, only 160 were viable, and of the 600 collected directly from the mother tree, 285 were viable, 125 more seeds than those collected on the ground. Because of this, we can see that the simple act of not opening the Sucupira-Branca fruits to remove the seed before planting, which is very common, may be linked to the low germination rate of the species, as this attribute may be related to the viability of its seeds, which is also very low. The characteristic can only be evaluated through the opening of the fruits. We can conclude that a factor that is connected with the low viability of the seeds and possibly also with the low germination is the place where they are collected, which, because of the results found, we can observe that the collection of the Sucupira-Branca fruits carried out directly from the matrix tree presents greater seed viability, and may also present a higher germination rate. DOI:https://doi.org/10.56238/devopinterscie-188